Experimental study on the dynamic performance of a novel system combining natural ventilation with diffuse ceiling inlet and TABS. (1st May 2016) - Yu, Tao; Heiselberg, Per; Lei, Bo; Zhang, Chen; Pomianowski, Michal; Jensen, Rasmus
Highlights: Dynamic experiments are performed to study energy performance of a new HVAC system. Designed control strategies show good utilization of natural ventilation cooling. TABS work well with the diffuse ceiling in the dynamic measurements. No local thermal comfort problem is found even in the extreme winter case. Designed control strategies can be used in the future application of this system. Abstract: This paper investigates the dynamic cooling performance of a novel system combining natural ventilation with diffuse ceiling inlet and thermally activated building systems (TABS). This system is tested in the lab under three climatic conditions representing typical seasons in Denmark, including a typical winter day, a typical day in the transitional season and a typical summer day. The corresponding dynamic control strategies have been designed for these three cases in the measurements. In the winter case, TABS have to be activated for two hours to supply extra heating to ensure a comfortable indoor environment. In the case representing the transitional season, changing the ventilation rate during both occupied and un-occupied hours can ensure the thermal autonomy of the room without extra heating or cooling from TABS. In the summer case, the free cooling potential of ventilation air is limited due to the relatively high inlet air temperature. Therefore, TABS are activated for ten hours to supply the extra cooling. Due to the use of the diffuse ceiling, the whole-body and local thermal comfort conditions are quite good in the measurements. The dynamic measurements in the paper are beneficial to the future design and application of this system.